Characterization of Magnetite and Hematite Using Infrared Spectroscopy - SihamMohammed HassenMohammed (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2018)
In this work, Infrared spectroscopy has been carried out to characterize the composition of the as-prepared samples in magnetite and hematite. The infrared spectra presented in this work were recorded in the range from 400 to 4000 cm-1 with FT-IR spectrometer. Infrared light is guided through an interferometer and then through the sample (or vice versa). A moving mirror inside the apparatus alters the distribution of infrared light that passes through the interferometer. The results obtained showed that the characteristic bands of magnetite and hematite are appeared in the spectra of two samples. Characteristic bands of hematite appeared in spectra of magnetite. Besides other materials appear in spectra of the two samples as, sulphate, water, silica and carbonate. Infrared spectroscopy proved to be easy and fast methods for the identification of characterization composition in hematite, magnetite samples and could be used for other materials.